The structure of cognitive and affective factors related to students' cognitive performance in language and maths - Δερμιτζάκη, Ειρήνη; Ευκλείδη, Αναστασία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF